Analisis Perilaku Pembeli Terhadap Skincare - Nurhasanah, Siti; Tripuspitasari, Yosi; Hidayat, Syamsul (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This research aims to analyze buyer behavior towards skincare products, with a focus on factors that influence purchasing decisions, product preferences, the influence of social media, and promotional strategies. This study uses a quantitative approach with survey methods to collect data from respondents regarding habits, preferences and external influences in purchasing skin care products. Data analysis techniques are carried out descriptively to identify trends and patterns of consumer behavior. The research results show that product quality is the main factor in decisions (91.3%), followed by needs and price. TikTok emerged as the top platform for seeking information (77.9%), while influencer reviews had a significant influence with 91.3% of respondents considering them before purchasing a product. The majority of consumers prefer local products (60.6%) compared to imports. Additionally, promotional strategies such as discounts and cashback proved effective in attracting attention, with 93.3% of respondents expressing interest in the offer. This research concludes that skincare buyer behavior is influenced by a combination of rational and emotional factors, which are strengthened by the influence of social media and promotions. These findings provide insight for producers in designing marketing strategies that are more effective and in line with consumer needs.